No evidence of cardiac stunning or decoupling immediately after cardiopulmonary bypass for elective coronary surgery. Issue 8 (28th May 2020) - Dybos Tannvik, Tomas; Kiss, Gabriel; Torp, Hans; Eskeland Rimehaug, Audun; Kirkeby‐Garstad, Idar
Abstract : Background: There is significant uncertainty regarding the timing of onset of cardiovascular stunning after cardiac surgery. Cardiovascular stunning is affecting both contractility (Ees) and arterial load. Arterial load may be represented by arterial elastance (Ea) and participates in ventriculo‐arterial coupling through the Ea/Ees ratio, giving information on efficiency and performance. An alternative approach to ventriculo‐arterial interaction is oscillatory power fraction (OPF). The aim of this study was to investigate the immediate beat‐to‐beat effects of on‐pump coronary artery bypass graft (CABG) surgery on contractility, cardiac power parameters, arterial load and ventriculo‐arterial coupling as well as classical haemodynamic parameters. Methods: We included 41 patients scheduled for fast‐track CABG surgery. Measurements were taken before and after cardiopulmonary bypass. A flow and pressure curve were recorded from transoesophageal pulsed wave Doppler and a radial artery catheter, respectively. This enabled the calculation of stroke work, total cardiac energy delivery, OPF and Ea/Ees ratio. Routine haemodynamic monitoring provided the classical haemodynamic parameters. Results: Immediately after cardiopulmonary bypass there was no firm evidence for alterations in contractility, stroke work, stroke volume or arterial elastance. Ea/Ees ratio and OPF remained unchanged. Conclusions: There was no evidence for clinically relevant cardiac stunning or altered arterial load immediately after cardiopulmonary bypass for CABG surgery. The unchanged Ea/Ees ratio and OPF are indicating unchanged cardiac efficiency before and after cardiopulmonary bypass. This indicates that in elective CABG patients cardiovascular stunning is perhaps a phenomenon of inflammation and not immediate ischaemia–reperfusion injury or mechanical handling.